Gene expression alterations in ulcerative colitis patients after restorative proctocolectomy extend to the small bowel proximal to the pouch. Issue 5 (30th June 2014) - Yanai, Henit; Ben-Shachar, Shay; Baram, Liran; Elad, Hofit; Gitstein, Gilad; Brazowski, Eli; Tulchinsky, Hagit; Pasmanik-Chor, Metsada; Dotan, Iris
Abstract : Objectives: To evaluate molecular profiles in the small bowel (SB) mucosa proximal to the pouch in ulcerative colitis (UC) patients after pouch surgery. Design: Patients were prospectively recruited and stratified according to disease behaviour: normal pouch (NP), chronic pouchitis (CP), and Crohn's-like disease of the pouch (CLDP). Biopsies obtained from the pouch and the normal-appearing proximal SB (40 cm proximal to the anal verge) were compared to ileal biopsies from normal controls (NC). A histopathological score based on the degree of polymorphonuclear and mononuclear infiltrates was used to assess inflammation in the pouch and the proximal SB. Gene expression analysis was performed using microarrays, and validated by real-time PCR. Gene ontology and clustering were evaluated by bioinformatics. Results: Thirty-six subjects were recruited (age 18–71 years, 16 males). Histopathology scores demonstrated minimal differences in the normal-appearing proximal SB of all groups. Nonetheless, significant (fold change ≥2, corrected p [FDR] ≤ 0.05) molecular alterations in the proximal SB were detected in all groups (NP n=9; CP n=80; and CLDP n=230) compared with NC. The magnitude of DUOX2 alteration in the proximal SB was highest. An increase of 6.0, 9.8 and 21.7 folds in DUOX2 expression in NP, CP, CLDP, respectively was observed. This was followed by alterations in MMP1, SLC6A14 and PGC. Gene alterations in the proximal SB overlapped with alterations within the pouch (76% and 97% overlap in CP and CLDP, respectively). Gene ontology analysis in the proximal SB and pouch were comparable. Conclusions: Significant gene expression alterations exist in an apparently unaffected proximal SB. Alterations in the pouch and the proximal SB were comparable, suggesting that inflammation may not be limited to the pouch, but that it extends to the proximal SB.